Effects of drying methods and solvent extraction on quantification of major bioactive compounds in pomegranate peel waste using HPLC - Nishant Kumar; Pratibha; Neeraj; Rokayya Sami; Ebtihal Khojah; Amani H. Aljahani; Amina A. M. Al-Mushhin (Scientific Reports, 2022)
Abstract Bioactive compound characterization is an essential step for utilizing pomegranate peel waste as food and nutraceuticals ingredients. In the present investigation, the effects of different drying methods (freeze, tray-oven, and sun) and extraction solvents such as methanol, ethanol, water, acetone, and hexane were investigated on the extraction and recovery of major bioactive compounds (ellagic acid, gallic acid, quercetin, and punicalagin) of pomegranate peel for two pomegranate varieties (i.e., Bhagwa and Ganesh) using high-performance liquid chromatography (HPLC). The results indicated that the freeze dried pomegranate peel powder of both pomegranate varities potential to extraction higher amount of bioactive compounds with methanol as extraction solvent as compared to other drying methods and solvents. Freeze-dried peel powder of Bhagwa pomegranate showed a higher amount of gallic acid (32.2 mg/g), ellagic acid (13.6 mg/g), punicalagin (15.2 mg/g), and quercetin (2.5 mg/g) with methanol solvent as compared to the other extract of Bhagwa and Ganesh varieties. The basis on the results of the current study, it can be concluded that the freeze-drying method of drying pomegranate peel powder and methanol as an extraction solvent are effective to recover higher amounts of bioactive compounds that can be utilized in food and pharmaceutical sectors at commercial scale.